AN AUDIT OF LENGTH OF BONE MARROW TREPHINE BIOPSIES AT A TERTIARY CARE HOSPITAL - Rehman, Saif ur; Zafar, Lubna; Kazi, Faiza; Rehman, Zahur ur; Luqman, Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Bone marrow trephine biopsy is a well established minor surgical procedure for the inspection of bone marrow usually done along with bone marrow aspiration. The objective of this study was to evaluate the length of trephine biopsies and the rate of positivity for diagnosis as well as unfit biopsies in various length ranges. Methods: This retrospective study was conducted at Fauji Foundation Hospital and Foundation University Medical College Rawalpindi from Jan 2007 to Dec 2009. A total of 394 trephine biopsy reports were collected and reviewed. The criterion for adequate trephine biopsy was ‰¥1.5 Cm. The biopsies were divided into four groups according to length, i.e., group-1: ‰¥1.5 Cm, group-2: 1-1.4 Cm, group-3: 0.5-0.9 Cm, and group-4: <0.5 Cm. The adequacy of trephine biopsy length and rate of positive diagnosis as well as unfit biopsies were compared. Results: Total 394 trephine biopsies were reviewed. Group-1 included 88 biopsies and 87 (98.9%) had positive diagnosis. Group-2 included 137 biopsies and 133 (97.1%) had positive diagnosis. Group-3 included 99 biopsies and 91 (92%) had positive diagnosis. Group-4 included 70 biopsies and 57 (81.4%) had positive diagnosis. There was no significant difference between group-1 and group-2 for the rate of positivity of diagnosis (p=0.65). In group-1, 1 (1.1%) was unfit for evaluation, in group-2, 4 (2.9%) were unfit, in group-3, 8 (8%) were unfit, and in group-4, 13 (18.5%) were unfit for evaluation. Total 26 trephine biopsies were unfit for evaluation, out of which 13 (50%) belonged to group-4. Trephine biopsies that were unfit for evaluation were 4 (4.9%) in 2007, 17 (10.5%) in 2008, and 5 (3.3%) in 2009. Conclusion: Although 22.3% biopsies were of recommended length there was no significant difference in rate of positive diagnosis between biopsies of ‰¥1.5 Cm and 1-1.4 Cm. Keywords: Audit, Bone marrow trephine biopsy